Effect of particulate air pollution and passive smoking on surrogate biomarkers of endothelial dysfunction in healthy children. (August 2014) - Kelishadi, Roya; Hashemi, Mohammad; Javanmard, Shaghayegh Haghjooy; Mansourian, Marjan; Afshani, Mohammadreza; Poursafa, Parinaz; Sadeghian, Babak; Fakhri, Maryam
<x content-type="archive" xml:space="preserve">Abstract</x> Background: This study aimed to determine the association of ambient particulate matter (PM) on surrogate markers of endothelial function and inflammation in healthy children with or without exposure to second-hand smoke. Methods: This cross-sectional study was conducted in 2011 in Isfahan, which is the second largest and second most air-polluted city in Iran. The areas of the city with lowest and highest air pollution were determined, and in each area, 25 pre-pubescent boys with or without exposure to daily tobacco smoke at home were selected, i.e. 100 children were studied in total. Serum levels of C-reactive protein (CRP) and nitric oxide (NO) were measured. Results: Mean (SD) NO concentration was 7·87 (2·18) and 7·75 (2·04) μmol/L for participants not exposed and exposed to passive smoking, respectively, which is not statistically significant. The corresponding figures for CRP concentrations were 1·69 (0·89) and 2·13 (1·19) μg/ml (P = 0·04). Mean (SD) CRP concentration was significantly higher in children living in the highly polluted area than in those in the area of low pollution [2·11 (1·91) vs 1·60 (1·43) μg/ml, respectively, P = 0·02]. This difference was not significant for NO concentration. The regression analysis that examined the association between PM concentration (as independent variable) and CRP and NO levels (as dependent variables) in children not exposed to passive smoking demonstrated that increased PM was associated with a decrease in NO and an increase in CRP concentration. This finding shows that, regardless of passive smoking, PM10 concentration has a significant independent association with serum CRP and is inversely associated with NO levels. Conclusion: The findings suggest that in healthy children PM concentration has a significant independent association with biomarkers of endothelial dysfunction and inflammation.